Congenital Heart Disease from Infancy to Adulthood: Pathology and Nosology - Gaetano Thiene; Marny Fedrigo (Biomedicines)
Congenital heart diseases (CHDs) are usually defined as structural anomalies of the heart and great arteries, present since birth, that are due to embryological maldevelopment, with overt or potential dysfunction. Nowadays, most of the patients with CHD in adulthood (age > 18 years) had been operated on with success in infancy or childhood and undergo periodical screening. Pathology and nosology of CHDs are herein treated with special attention to adulthood according to the involved cardiac structures (aorta, valves, coronary arteries, myocardium, great arteries, conduction system). Moreover, the purpose is to postulate, in the era of molecular medicine, that genetically determined defects are also congenital cardiac disorders, with or without structural abnormality, and should be defined CHDs as well since their molecular background is material and present since conception.